Water and Sanitation: Achievement of Large Indian States. Issue 1 (April 2021) - Agarwal, Manmohan; Saha, Rimon
In this paper we make a comparative analysis of water and sanitation facilities across Indian states. We also analyse the trend and pattern of state expenditure in the water and sanitation sector and relate the expenditure with the nature of the existing facilities. Furthermore, we assess whether the state governments are adequately financing the sector in accordance to their GDP. Using data from the state statistical reports during 2001–2012, we find that the sanitation facilities are alarmingly low, particularly in the states Assam, Bihar and Madhya Pradesh. There are high interstate disparities in drainage facilities and latrine usage, with no sign of convergence during the study period. However, in terms of the provision of sanitation facilities, Haryana has showed significant progress over the years, whereas the progress in Assam, Rajasthan and Maharashtra does not seem promising. Along with the poor facilities, state spending for the provision of such facilities is also limited. We find that the correlation between expenditure and the facilities is also not direct and strong. Lastly, we notice the extent of expenditure in accordance with their gross state domestic product is astonishingly low for most of the states except Haryana.